Rigid block and spring homogenized model (HRBSM) for masonry subjected to impact and blast loading - Silva, Luis C. (2017)
In the present study, a simple and reliable Homogenization approach coupled with a Rigid Body and Spring Model (HRBSM) accounting for high strain rate effects is utilized to analyse masonry panels subjected to impact and blast loads.The homogenization approach adopted relies into a coarse FE discretization where bricks are meshed with a few elastic constant stress triangular elements and joints are reduced to interfaces with elasto-plastic softening behaviour including friction, a tension cut-off and a cap in compression. Flexural behaviour is deduced from membrane homogenized stress - strain relationships by on - thickness integration (Kirchhoff- Love plate). Strain rate effects are accounted for assuming the most meaningful mechanical properties in the unit cell variable through the so-called Dynamic Increase Factors (DIFs), with values from literature data. The procedure is robust and allows obtaining homogenized bending moment/torque curvature relationships (also in presence of membrane pre - compression) to be used at a structural level within the HRBS model, which has been implemented in a commercial software. At structural level, the approach resorts to a discretization into rigid quadrilateral elements with homogenized bending/torque non-linear springs on adjoining edges.The model is tested on a masonry parapet subjected to a standardized impact and on a rectangular masonry slab subjected to a blast load. In both cases, a number of previous results obtained by literature models are available for comparison, as well as experimental data. Satisfactory agreement is found between the present results and the existing literature in the field, both experimental and numerical.